Potential for Single-Case Evaluation in Employment Services : Goal Attainment Scaling Method for Difficult-to-Employ Jobseekers - Piirainen, Keijo (Diakonia-ammattikorkeakoulu, 2015)
Individual goal-setting in services is not a new topic. Goal-oriented work and the need for such are brought up for discussion occasionally. At the same time, it is usually mentioned that it is important to evaluate the attainment of goals. Goal Attainment Scaling (GAS) is a single-case evaluation method developed for individual goal-setting and the evaluation of effects. The Social Insurance Institution of Finland (Kela) has introduced the method for use in their rehabilitation services. This publication evaluates the prerequisites of the employment and economy administration for the use of this method in client work, particularly with those people who are difficult to employ. Attention is paid especially to services arranged by the employment administration, whose baseline situation is compared to Kela. There were interviews of 21 experts conducted for the purposes of this study. This evaluation was conducted under the project Worthwhile Employment Services funded by North Karelia Centre for Economic Development, Transport and the Environment and implemented by Diaconia University of Applied Sciences, Research and Development Services for Social and Health Economics. Many factors limit the possibilities for individual goal-setting and evaluation of effects. First of all, goal-setting and evaluation of effects require sufficient training. Secondly, the use of a tool such as GAS requires that professionals have sufficient time available to meet with their clients. Clients are often difficult to employ and their circumstances require thorough clarification. Thirdly, individual goal-setting and evaluation of effects require that clients can obtain focused guidance and support from within the service to which they are directed. Fourthly, the infrastructure to support individual goal-setting and evaluation of effects must be in proper condition. For example, logging procedures and the maintenance of registries must be structured so that they can yield other information in addition to that relating to employment ...